Hypomagnesaemia in adult patients of newly detected type-2 diabetes mellitus - Nasreen, Tania; Parvin, Farida; Zohra, Fatima Tuz; Sultana, Gazi Sharmin (Pulse, 2024)
Background: Magnesium (Mg++) deficiency is related with terrible glycemic control. Supplementation of Mg++ lowers blood sugar, improves insulin sensitivity and as a end result, diabetic complications inclusive of diabetic nephropathy, diabetic neuropathy, diabetic retinopathy are delayed. Objective: This study was designed to know the status of serum Mg++ in newly detected type 2 diabetic subjects. Methodology: The study was conducted at the Department of Laboratory Medicine (Clinical Pathology) in collaboration with BIRDEM General Hospital, Dhaka. In this study, serum magnesium level of one hundred twenty newly detected type 2 diabetic patients were measured. The test was achieved by biochemical auto analyzer (Siemens Dimension RL Max). Result: The mean magnesium level was 1.9±3.1 mg/dl with range from 1.5-2.4 mg/dl. Hypomagnesemia (Serum magnesium < 1.8 mg/dl) was documented in 36 (30%) patients with a female: male ratio of 5:7. 32(89.7%) patients had raised HbA1c in low magnesium group. 60 (71.0%) patients had raised HbA1c in normal magnesium group. The difference was statistically significant (p<0.05) between two groups. Conclusion: Measurement of serum concentration of magnesium is easy and not expensive. Therefore, treatment with these trace elements should be started in all newly detected type 2 diabetic patients. Pulse Vol.16, 2024 P: 22-25